Criterios teóricos - jurídicos en l indemnización por responsabilidad civil extracontractual derivados de un accidente de tránsito - Cabanillas Vásquez, Wilmer César (2019)
ABSTRACT We investigated the theoretical and legal criteria that the judge must observe to determine the amount of compensation for damages caused to the human person, in case of non-contractual civil liability, arising from a traffic accident. The study sample consisting of 05 relevant case-law judgments was intentionally chosen in order to determine the legal-legal criteria that the Judge observes to determine the amount of compensation for non-contractual civil liability in cases of traffic accidents, as well as the table of indemnifying amounts of the Compulsory Traffic Accident Insurance, the death indemnities fixed by the Peruvian courts in the processes for traffic accidents, and the compensation for damages in the comparative legislation, in order to verify the indemnity amounts for reparation to the victim, in the 2010-2017 period; likewise, comparative jurisprudence was considered. For the collection of information, the techniques of documentary analysis and observation were considered, which were applied with their respective instruments; the data obtained were organized and presented in frequency tables. For the discussion of the results, the methods analysis synthesis, inductive deductive, descriptive and hermeneutic were used, in order to study the variables of the problem, interpret the rules and infer the conclusions and generalize the results to the study population. It was concluded that the theoretical-juridical criteria applied in Peruvian processes to determine the amount of compensation for damages caused to the human person, in case of extracontractual civil liability, derived from a traffic accident are applied indistinctly as they are : emerging damage, lost profits, moral damage, biological damage, damage to the life project, damage to work capacity, damage to health or well-being and damage to successors, although the criteria of reasonableness and proportionality.